Does workplace health promotion reach shift workers? - Kirsten Nabe-Nielsen; Anne Helene Garde; Thomas Clausen; Marie Birk Jørgensen (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: One reason for health disparities between shift and day workers may be that workplace health promotion does not reach shift workers to the same extent as it reaches day workers. This study aimed to investigate the association between shift work and the availability of and participation in workplace health promotion. METHODS: We used cross-sectional questionnaire data from a large representative sample of all employed people in Denmark. We obtained information on the availability of and participation in six types of workplace health promotion. We also obtained information on working hours, ie, fixed day work (reference) and shift work (four categories), psychosocial work factors, and health behaviors. We conducted binary logistic regression analyses both in the total sample (N=7555) and in a sub-sample consisting of job groups with representatives in all shift work categories (N=2064). RESULTS: In the general working population, fixed evening and fixed night workers, and employees working variable shifts including night work reported a higher availability of health promotion, while employees working variable shifts without night work reported a lower availability of health promotion. Within job groups undertaking shift work, we found few differences between day and shift workers, and these few differences appear to favor shift workers. Day workers and shift workers did not differ significantly with respect to their participation in health promotion. CONCLUSIONS: The present study could not confirm that shift workers in general report a lower availability of and participation in workplace health promotion.